PERKEMBANGAN TEORI VYGOTSKY DAN IMPLIKASI DALAM PEMBELAJARAN MATEMATIKA DI MIS RAJADESA CIAMIS - Fitri Fitriani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
One of the phases in child development is cognitive development. This cognitive development is based on the opinion that cognitive abilities are fundamental in guiding children's behavior. Cognitive development began to be studied in the middle ages when scientific advances rose. Vygotsky's cognitive theory states that children's knowledge is obtained through social interaction activities among individuals or between individuals and groups and in an environment. Several Vygotsky theories applied in the classroom learning include ZPD scores of children; it is not the Intelligence Quotient (IQ) but the use children's learning proximal development zone. According to this theory, children learn through more skilled peers as teachers, who monitor and help children use private speech and place teaching in a different context. Learning becomes meaningful and useful if children are trained to use thinking tools. For example, children can solve problems, make it easier for them to act, expand their thinking, and do something according to their natural capacity. The method used was descriptive qualitative research with data collection through observations, interviews, and documentation.